2021
DOI: 10.1016/s2213-2600(21)00175-2
|View full text |Cite
|
Sign up to set email alerts
|

Changes in in-hospital mortality in the first wave of COVID-19: a multicentre prospective observational cohort study using the WHO Clinical Characterisation Protocol UK

Abstract: Background Mortality rates in hospitalised patients with COVID-19 in the UK appeared to decline during the first wave of the pandemic. We aimed to quantify potential drivers of this change and identify groups of patients who remain at high risk of dying in hospital. MethodsIn this multicentre prospective observational cohort study, the International Severe Acute Respiratory and Emerging Infections Consortium WHO Clinical Characterisation Protocol UK recruited a prospective cohort of patients with COVID-19 admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
76
3
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(92 citation statements)
references
References 21 publications
9
76
3
4
Order By: Relevance
“…The in-hospital mortality of 9.5% during the first wave is lower than the in-hospital mortality rate of the first wave from other countries and centres: for example, 22% in Germany [14], 30% in the UK [15] and 18.7% in Denmark [16]. A study from Geneva (Switzerland) reported an inhospital mortality of 15.6% [17].…”
Section: Discussionmentioning
confidence: 90%
“…The in-hospital mortality of 9.5% during the first wave is lower than the in-hospital mortality rate of the first wave from other countries and centres: for example, 22% in Germany [14], 30% in the UK [15] and 18.7% in Denmark [16]. A study from Geneva (Switzerland) reported an inhospital mortality of 15.6% [17].…”
Section: Discussionmentioning
confidence: 90%
“…This comment applies also to [ 22 ], published after the submission of the first version of the present paper. This last reference focuses on the temporal evolution of risks of severe events, in the same spirit as [ 23 , 24 ]. The last two papers are based on large cohorts, but the simple modeling approach used there does not allow to account, for instance, for the evolution of the length of stay in hospital or ICU.…”
Section: Discussionmentioning
confidence: 99%
“…11 Data suggest that although COVID-19 is usually milder if contracted after vaccination than in unvaccinated individuals, mortality remains high in hospitalised individuals: data from the International Severe Acute Respiratory and Emerging Infection Consortium have shown a mortality of 27·0% (400 of 1482 died) in individuals hospitalised with COVID-19 in the UK more than 21 days after vaccination, similar to mortality rates observed during the first wave (March–April, 2020). 12 , 13 …”
Section: Introductionmentioning
confidence: 99%